Answer:
A
Explanation:
The polynomial (x+4)(x-1)(x-2)(x-4) has zeros at x=-4,1,2,4.
The related polynomial equation is (x+4)(x-1)(x-2)(x-4)=0.
In order for this equation to be true at least one of the factors must by 0 that is the only way a product can be zero (if one of it's factors is).
So you wind up needing to solve these 4 equations:
x+4=0 x-1=0 x-2=0 x-4=0
x=-4 x=1 x=2 x=4
First equation, I subtracted 4 on both sides.
Second equation, I added 1 on both sides.
Third equation, I added 2 on both sides.
Fourth equation, I added 4 on both sides.
-4,1,2,4 are all integers
Integers are real numbers.
So A.